2018
DOI: 10.9778/cmajo.20170110
|View full text |Cite
|
Sign up to set email alerts
|

Immersive and interactive virtual reality to improve learning and retention of neuroanatomy in medical students: a randomized controlled study

Abstract: Background: Spatial 3-dimensional understanding of the brain is essential to learning neuroanatomy, and 3-dimensional learning techniques have been proposed as tools to enhance neuroanatomy training. The aim of this study was to examine the impact of immersive virtual-reality neuroanatomy training and compare it to traditional paper-based methods. Methods:In this randomized controlled study, participants consisted of first-or second-year medical students from the University of Saskatchewan recruited via email … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
141
1
9

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(158 citation statements)
references
References 28 publications
7
141
1
9
Order By: Relevance
“…There is emerging evidence suggesting that virtual interactive tools may be useful and accessible to support early academic development [2,3]. In fact, different studies have been published about resident learning principles, stating that the more the process is both physical and mental, the more it is efficient [2,3].…”
mentioning
confidence: 99%
“…There is emerging evidence suggesting that virtual interactive tools may be useful and accessible to support early academic development [2,3]. In fact, different studies have been published about resident learning principles, stating that the more the process is both physical and mental, the more it is efficient [2,3].…”
mentioning
confidence: 99%
“…Due to this distinct experiential quality, VR can augment learning with an immersive experience. In addition, VR has been shown to improve learning outcome gains [29-31], and, compared with educational videos, VR has been shown to increase engagement, positive emotions, and remembering of the presented information [32,33]. In fact, an increasing number of classrooms are utilizing VR technology to provide unique and effective educational experiences for their students [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…This paper describes our study, including some of its initial quantitative findings. Very few studies of this kind have been previously reported (see [5,6]). In some respects, the most similar has been that of Madden et al [13] that involved 3 conditions (normal lab, desktop app, and VR app) with a pre/post assessment model employing isomorphic sets of questions.…”
Section: Introductionmentioning
confidence: 99%